Crevasse pattern evolution in response to paraglacial processes at three outlet glaciers Tungnakvíslarjökull, Steinsholtsjökull and Sólheimajökull in South Iceland from 1945 to 2022 - Sinah Toschka 1990- (2023)
Paraglacial processes play an important role in many regions worldwide and their importance increases with ongoing climatic changes. Crevasses within glaciers are very sensitive to changes within the stress field of the glacial ice and it is therefore suggested that past or ongoing slope instabilities can be detected in the crevasse pattern evolution. To investigate this, crevasses of three outlet glaciers in South Iceland were mapped based on aerial images between the years 1945 until 2022 and their crevasse evolution was studied. At the Steinsholtsjökull outlet glacier, located in the Northern part of the Eyjafjallajökull ice cap, a rockslide event in 1967 fell on top of the glacier, producing rockslide parallel features within the ice. Subsequently a glacial lake outburst flood (GLOF) was triggered which affected the whole Steinsholtsdalur valley as well as the outwash plain. The Tungnakvíslarjökull outlet glacier, Northwest of the Mýrdalsjökull ice cap, is affected by a deep seated gravitational slope deformation (DSGSD) on its Northern slope that has been in motion since at least 1945. Lastly, the Sólheimajökull outlet glacier, Southwest of Mýrdalsjökull, is not connected to any slope deformation. The results show that Steinsholtsjökull recovered quickly, within 13 years, from the changes in the ice and re-established crevasse patterns typical for valley glaciers. Increased input of debris and boulders on the glacier margins that lead to uneven glacier bed topography and therefore irregular crevasse patterns are present at Steinsholtsjökull as well as Tungnakvíslarjökull. No unusual crevasse patterns that would indicate any slope movements were detected at Sólheimajökull. The study has therefore shown that glaciers can recover quickly from disturbances, especially during advance periods, but that increased debris deposition, mostly along the glacial margins, can create long lasting changes within the crevasses. Landmótunarferli á svæðum þar sem jöklar hafa hopað eru mikilvæg og mun vægi þeirra verða meira ...